Cervical spondylosis: analysis of clinical and radiological correlation - K., RoseBist P.; Peethambaran, Anil Kumar; Peethambar, Gowri Anil (International Surgery Journal, 2018)
Background: Cervical spondylosis is a chronic degenerative lesion of the cervical intervertebral discs causing axial neck pain, cervical radiculopathy and myelopathy. This study was undertaken to study the clinical and radiological correlation in cervical spondylosis with respect to clinical and radiological findings. Methods: A prospective observational study was done on 100 patients with cervical spondylosis treated in a tertiary care centre of South Kerala. The sociodemographic details, clinical and radiological findings were recorded. Nurick’s grading and Modified Japanese orthopaedic association cervical spine myelopathy scoring was done. Data collected was analyzed using Microsoft Excel 2010 and results expressed in proportions. Results: Maximum prevalence was seen in 40-49 years group with male predominance. Majority of the patients had neck pain, sensory numbness and motor weakness. Spurling’s sign and Lhermitt’s sign was positive in 60% and 47% patients respectively. Complete paralysis was seen on both sides in 12% patients at wrist joint and 9% each in elbow and knee joints. Grade II cervical spondylosis was seen in 43%. Modified Japanese orthopaedic association score was less than 18 in all patients. Canal size was reduced in many. The clinical and radiological findings were consistent. Conclusions: Cervical spondylosis is seen in those above 30 years of age with male predominance. Clinical and radiological findings are consistent with each other. Further studies are advised for better correlation.